The Double Dominion Over Women's Bodies as a barrier to exercising sexual and reproductive rights: a mixed-methods study in La Ladrillera, México - Bejarano Zambrano, Claudia Lizeth; Gilbert, Hannah; González Palacios, Carlos Antonio; Mukherjee, Joia; Bejarano Zambrano, María Fernanda; Nadeem Kasmani, Muhummed; Knipper, Michael (My University, 2026)
Background Sexual and reproductive health and rights (SRHR) are essential to women’s autonomy and well-being. Despite global recognition of SRHR as a cornerstone of public health and human rights, research and policy have often failed to account for the lived realities that impede access to SRHR for women on the urban periphery or in rural settings. This study aims to explore how deleteriously interacting social and structural factors shape access to SRHR. Methods A convergent mixed-methods study was conducted in La Ladrillera, a brickmaking community in Baja California, Mexico. Quantitative surveys were administered to all adult women in the community using an adapted reproductive health toolkit, and descriptive statistical analyses were conducted. In-depth interviews were held with women, and a focus group with male community members. Qualitative data were analyzed using an inductive content analysis approach. A feminist and rights-based thematic analysis was employed to examine intersecting social, relational, and institutional determinants of SRHR. Findings All adult women in the community (35) completed the survey, 18 participated in interviews, and six men took part in the focus group discussion. The women’s average age was 43⋅1 years (range 18–84). Participants were asked about Indigenous affiliation; only one reported partial Huichol heritage, and no other racial or ethnic identities were reported. The data revealed that women’s SRH experiences are constrained by patriarchal power in both private and public spheres. While quantitative data supported these findings, they were especially clear in the qualitative component, where many women described how intimate relationships frequently limit contraceptive decision-making and pressure young women into early partnerships. Simultaneously, healthcare providers often disregard informed consent and prioritize provider authority over women’s preferences. These overlapping mechanisms of control reflect symbolic and structural violence, perpetuating reproductive inequities. Interpretation Barriers to SRHR in underserved communities extend far beyond logistics or service availability; they are embedded in everyday practices of domination and neglect. Rights-based, context-informed interventions that actively engage women’s voices, especially in clinic and community settings, are critical. Our findings underscore the need for innovative, feminist-informed approaches to SRHR that confront gendered power structures and center community-led solutions. Funding This work was conducted with support from the Harvard Medical School Master of Medical Sciences in Global Health Delivery program, Harvard University, and the Ronda Stryker and William Johnston MMSc Fellowship.
THE LANCE Regional Health
Keywords: violence; Gender-base violence; Sexual and reproductive rights; Reproductive right; Patriarchy; Womens health; México; Health system; Mixed-methods study; Structural violence; Campus Mexicali